2020
DOI: 10.1175/jtech-d-19-0146.1
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Network for Cloud-to-Ground Lightning Nowcasting with Multisource Data

Abstract: Precise and timely lightning nowcasting is still a great challenge for meteorologists. In this study, a new semantic segmentation deep learning network for cloud-to-ground (CG) lightning nowcasting, named LightningNet, has been developed. This network is based on multisource observation data, including data from a geostationary meteorological satellite, Doppler weather radar network, and CG lightning location system. LightningNet, with an encoder–decoder architecture, consists of 20 three-dimensional convoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 57 publications
(72 reference statements)
1
46
0
1
Order By: Relevance
“…Compared with the ConvLSTM‐based models, the U‐Net has more flexible architecture, which can be easily adjusted for exploiting multiple input information. The U‐Net is increasingly used by spatiotemporal forecasting studies, such as nowcasting of lightnings (Zhou et al., 2020) and global weather forecasting (Weyn et al., 2020). As such, we choose U‐Net as our backbone model in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the ConvLSTM‐based models, the U‐Net has more flexible architecture, which can be easily adjusted for exploiting multiple input information. The U‐Net is increasingly used by spatiotemporal forecasting studies, such as nowcasting of lightnings (Zhou et al., 2020) and global weather forecasting (Weyn et al., 2020). As such, we choose U‐Net as our backbone model in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations (Geng et al ., 2019; Wang et al ., 2019; Zhou et al ., 2020) have verified that integrating different data sources contributes to lightning forecasting. For example, (Wang et al ., 2019) designed a DNN model combining past observations and NWP to predict temperature, relative humidity and wind at an AWS.…”
Section: Discussionmentioning
confidence: 80%
“…They demonstrated that information fusion brings a significant performance improvement compared with the case using a single data source. (Zhou et al ., 2020) proposed a new semantic segmentation deep learning network for 1 hr cloud‐to‐ground lightning nowcasting. Their model displays good performance by introducing multi‐source data.…”
Section: Discussionmentioning
confidence: 99%
“…The recognition performances of the learning models on thunderstorms and gales were compared. Zhou et al (2020) proposed a new semantic segmentation-based deep learning network for cloud-to-ground lightning nowcasting named LightningNet. This model conducts reliable lightning nowcasting by using multisource data.…”
Section: Instructionmentioning
confidence: 99%